AI-driven education: shaping the future of learning with personalization and engagement - Ong, Yew-Soon (2024)
The widespread availability of data has created significant opportunities for the evolution of artificial intelligence (AI) in education. This rapid development is reshaping the role of modern educators, who must adapt their teaching practices to meet the demands of learners seeking more data-driven, personalized approaches to education. Professor Ong Yew Soon, President's Chair Professor of Computer Science at NTU and A*STAR's AI Chief Scientist, will share his innovative insights on integrating AI and blended learning in higher education. With over two decades of teaching experience, Prof. Ong believes that "there’s no incapable student, only an unmotivated one." Central to his talk is how AI has shaped his own teaching practices and the evolving relationship between technology and student engagement in today’s educational landscape. The session will also feature examples of generative AI in education and its impacts, offering a look at how AI-driven learning is influencing the future of education.